Problem of the diagnosis of acquired hemolytic anemia in childhood - S.O. Nykytyuk; M.M. Galych; N.B. Haliyash; Z.Ya. Borys; M.Y. Yatsiuk (Zaslavsky O.Yu., 2020)
Autoimmune hemolytic anemia is a heterogeneous group of diseases that are associated with decompensated acquired hemolysis. Autoimmune hemolytic anemia in children is most commonly observed after a viral illness. However, it is quite a rare disorder with the incidence of less than 0.2 cases per 100,000 of pediatric population. That is why the purpose of the article was to present a clinical case of autoimmune hemolytic anemia. A case of autoimmune hemolytic anemia in a 4-year-old boy is presented. On admission, he was diagnosed with acute viral infection with bilateral pneumonia and abdominal syndrome. While at hospital, the boy's condition has worsened dramatically: weakness and pallor of the skin increased rapidly. Complete blood count revealed progressive hemolytic anemia (Hb 57 g/l, erythrocytes 2.58 × 1012/l, Ht 0.16, leukocytes 13.88 × 109/l, erythrocyte sedimentation rate 69 mm/h, platelets 400 × 109/l). There was a moderate increase of bilirubin due to unconjugated fraction (31.3 and 21.2 µmol/l, respectively). The issue of hemotransfusion was raised, but as a result of the crossmatching compatibility test, 20 packages of same-group blood were rejected due to incompatibilities. Aggressive immunosuppressive therapy (integrated administration of high-dose corticosteroids combined with intravenous immunoglobulins at a dose of 2 g/kg/day) allowed hemolysis to be stopped, and patient's condition has improved, the issue of blood transfusion was rejected. The peculiarity of the presented case is a critical increase of anemia in the absence of classical signs of hemolysis, impossibility of hemotransfusion and a positive dynamics at prescription of high doses of corticosteroids and immunoglobulin. Thus, pediatricians should be aware of autoimmune hemolytic anemia, and it is important to increase their knowledge about the correct diagnostic algorithm in these cases. The drugs of choice for the treatment of autoimmune hemolytic anemia are intravenous immunoglobulins in immunosuppressive doses and a short course of glucocorticoids. In cases of resistance to such treatment, perftoranum transfusion is indicated.